Office Inventory Processing Information System at PT. Dian Ratna Abadi - Prananda, Ade Tya; Hadinata, Edrian; Sinaga, Tantri Hidayati (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2020)
PT. Dian Ratna Abadi is a company engaged in human resource services. At this time, inventory data collection is still done manually using Microsoft Office applications. Data collection in this way can make it difficult for employees to collect data and produce reports, so that it is not effective and efficient. The research method used is a descriptive method using observation data collection techniques, interviews and literature studies. This research is an Applied Research. The purpose of this research is to design a goods inventory application to provide convenience in processing data to obtain the desired information. From the research conducted, it produces an inventory system that can be used without any errors or errors in the system